1997
DOI: 10.1098/rstb.1997.0115
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and nitric oxide as effector molecules against parasitic infections

Abstract: SU M M A RYNitric oxide (NO) derived from L-arginine by the catalytic action of inducible NO synthase (iNOS) plays an important role in killing parasites. Many cell types express high levels of iNOS when activated by a number of immunological stimuli which include interferon-gamma (IFN-), tumour necrosis factor alpha, and lipopolysaccharide. IFN-is typically produced by the Th1 subset of CD4+ T cells, whose di¡erentiation depends on interleukin-12 (IL-12) produced by macrophages. Mice with a disrupted iNOS gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
2
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 43 publications
3
77
2
2
Order By: Relevance
“…Under different conditions, nitric oxide can have cytoprotective or cytotoxic effects depending not only on the initial insult but also on the source, rate of production, and concentration of nitric oxide in the biological milieu (Brunet et al 1999). Hence, it is the balance between nitric oxide and other inflammatory cytokines and mediators (such as TNF-a, IL-1ß, IFN-c) that is crucial in determining its effect on the host (Liew et al 1997). Several studies have suggested that nitric oxide plays a unique role in the liver, and its involvement in a variety of hepatic processes is supported by the finding that the majority of cells found in the liver, such as hepatocytes, Kupffer cells, fat-storing cells, and endothelial cells, are able to produce nitric oxide under adequate stimulation (Brunet et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under different conditions, nitric oxide can have cytoprotective or cytotoxic effects depending not only on the initial insult but also on the source, rate of production, and concentration of nitric oxide in the biological milieu (Brunet et al 1999). Hence, it is the balance between nitric oxide and other inflammatory cytokines and mediators (such as TNF-a, IL-1ß, IFN-c) that is crucial in determining its effect on the host (Liew et al 1997). Several studies have suggested that nitric oxide plays a unique role in the liver, and its involvement in a variety of hepatic processes is supported by the finding that the majority of cells found in the liver, such as hepatocytes, Kupffer cells, fat-storing cells, and endothelial cells, are able to produce nitric oxide under adequate stimulation (Brunet et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…macrophages, can express high levels of iNOS when activated by immunological stimuli, e.g. interferon gamma (IFN-c) or tumour necrosis factor (TNF), thus leading to the killing of parasites (Liew et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…and T. cruzi). 11 It appears that evolutionary diversity has been acquired at the level of the transcription factors involved in NO synthesis in response to different kinds of stress stimuli. Three forms have been described: neuronal (nNOS, NOS1), endothelial (eNOS, NOS3) and inducible (iNOS, NOS2).…”
Section: Nitric Oxide Productionmentioning
confidence: 99%
“…It has HELMINTHOLOGIA, 49, 4: 189 -200, 2012 In vivo inhibition of inducible nitric oxide synthase by aminoguanidine influences free radicals production and macrophage activity in Trichinella spiralis infected low responders (C57BL/6) and high responders (BALB/c) mice (Eisenstein et al, 1994;Rockett et al, 1994;Dai & Gottstein, 1999;Ren et al, 2008) and tissue pathology (Garside et al, 1992;Kolb & Kolb-Bachofen, 1992;Pacher et al, 2007). However, the role of NO in defence against T. spiralis and the other Th-2 inducing infections such as helminthoses have not been yet completely explained (James, 1995;Liew et al, 1997;Alonso-Trujillo et al, 2007;Gruden-Movsesijan & Sofronic-Milosavljevic, 2010). It is known that Th-2 immune response plays the main role during T. spiralis intestinal infection (Helmby & Grencis, 2003;Reiterová et al, 1999;Dvorožňáková et al, 2010).…”
Section: Introductionmentioning
confidence: 99%